Current distribution of the invasive mosquito species, Aedes koreicus [Hulecoeteomyia koreica] in northern Italy. Issue 1 (December 2015) - Montarsi, Fabrizio; Drago, Andrea; Martini, Simone; Calzolari, Mattia; De Filippo, Francesco; Bianchi, Alessandro; Mazzucato, Matteo; Ciocchetta, Silvia; Arnoldi, Daniele; Baldacchino, Frédéric; Rizzoli, Annapaola; Capelli, Gioia
Abstract Background The invasive speciesAedes (Finlaya )koreicus was first identified in north-eastern Italy in 2011, during the ongoing surveillance activity ofAedes albopictus . Following this finding, a more intensive monitoring was carried out to assess the distribution of the species and to collect biological data. Herein, we report the new records obtained by four years of surveillance. Findings The presence ofAe. koreicus was checked using ovitraps, adults traps and by larval collections in all possible breeding sites from May 2011 to July 2015. The monitoring started in the site of the first detection (Province of Belluno) and was then extended in the neighbouring Provinces belonging to four Regions.Aedes koreicus was found in 73 municipalities out of 155 monitored (47.1 %), including 23 municipalities (14.8 %) previously not infested. The area of first detection ofAe. koreicus (Province of Belluno) was also the most infested (68 %). However the mosquito has also been found to the west (Province of Trento) and to the south and south-west (Provinces of Vicenza and Treviso) of the initially infested area. Conclusions The spread ofAe. koreicus is directed towards south and west from the original infested area, likely due to the dense road connections and the habitat suitability of the new areas. According to these records, northern Italy has a high probability to be invaded byAe. koreicus in the next decade. These data can be useful to validate predictive models of potential distribution and dispersal of this species in Italy or in Europe.